An antibiofilm coating of 5‐aryl‐2‐aminoimidazole covalently attached to a titanium surface. Issue 6 (13th December 2018) - Peeters, Elien; Hooyberghs, Geert; Robijns, Stijn; De Weerdt, Ami; Kucharíková, Soňa; Tournu, Hélène; Braem, Annabel; Čeh, Katerina; Majdič, Gregor; Španič, Tanja; Pogorevc, Estera; Claes, Birgit; et al.
Abstract: Biofilms, especially those formed by Staphylococcus aureus, play a key role in the development of orthopedic implant infections. Eradication of these infections is challenging due to the elevated tolerance of biofilm cells against antimicrobial agents. In this study, we developed an antibiofilm coating consisting of 5‐(4‐bromophenyl)‐ N ‐cyclopentyl‐1‐octyl‐1 H ‐imidazol‐2‐amine, designated as LC0024, covalently bound to a titanium implant surface (LC0024‐Ti). We showed in vitro that the LC0024‐Ti surface reduces biofilm formation of S. aureus in a specific manner without reducing the planktonic cells above the biofilm, as evaluated by plate counting and fluorescence microscopy. The advantage of compounds that only inhibit biofilm formation without affecting the viability of the planktonic cells, is that reduced development of bacterial resistance is expected. To determine the antibiofilm activity of LC0024‐Ti surfaces in vivo, a biomaterial‐associated murine infection model was used. The results indicated a significant reduction in S. aureus biofilm formation (up to 96%) on the LC0024‐Ti substrates compared to pristine titanium controls. Additionally, we found that the LC0024‐Ti substrates did not affect the attachment and proliferation of human cells involved in osseointegration and bone repair. In summary, our results emphasize the clinical potential of covalent coatings of LC0024 on titanium implant surfaces to reduce the risk of orthopedic implant infections. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1908–1919, 2019.